Video by Artists - Askevold, David; Boyer, Jean-Pierre; Bronson, A. A.; Gale, Peggy; Graham, Dan; Levine, Les; Sherman, Tom (Art Metropole, 1976)
Ant Farm ; Askevold, David ; Campbell, Colin ; Druick, Don ; Emilson, Bruce ; General Idea ; Graham, Dan ; Harding, Noel ; Hayden, Michael ; Razutis, Al ; Steele, Lisa ; Trasov, Vincent ; Vazan, Bill ; W.O.R.K.S ; Watt, John ; Werden, Rodney
Bibliog. p. 216--223
Engels
boek